2005
DOI: 10.2116/analsci.21.115
|View full text |Cite
|
Sign up to set email alerts
|

Chiral CE Separation of Dopamine-Derived Neurotoxins

Abstract: An enantiomeric separation of dopamine-derived neurotoxins by capillary electrophoresis has been developed. Tetrahydroisoquinoline (TIQ), dopamine (DA), (R/S)-1-benzyl-TIQ (BTIQ), (R/S)-6,7-dihydroxy-1-methyl-TIQ (salsolinol, Sal), and (R/S)-6,7-dihydroxy-1, 2-dimethyl-TIQ (N-methyl-salsolinol, NMSal) were studied as model compounds. The CE running buffer (50 mM phosphate buffer at pH 3.0) contained 1.5 M urea and 12 mM β-CD as a chiral selector. During separation, the (R)-enantiomers formed more stable inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The elution time of the enantiomers was approximately 6.2 minutes for (S)-SAL and 7.4 minutes for (R)-SAL (Fig. 1a), which is in line with the elution patterns described by other authors using a similar HPLC system (Baum & Rommelspacher 1994;Deng et al 1995;Naoi et al 1996;Liu et al 2000;Tóth et al 2001;Quan et al 2005;Cai & Liu 2008;Rojkovicova et al 2008;Lee et al 2010). This elution pattern is also supported by compu- tational modeling, evaluating the total energy for stabilization, demonstrating that the complex formed by (R)-SAL and β-cyclodextrin is stronger than the complex of (S)-SAL and β-cyclodextrin.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The elution time of the enantiomers was approximately 6.2 minutes for (S)-SAL and 7.4 minutes for (R)-SAL (Fig. 1a), which is in line with the elution patterns described by other authors using a similar HPLC system (Baum & Rommelspacher 1994;Deng et al 1995;Naoi et al 1996;Liu et al 2000;Tóth et al 2001;Quan et al 2005;Cai & Liu 2008;Rojkovicova et al 2008;Lee et al 2010). This elution pattern is also supported by compu- tational modeling, evaluating the total energy for stabilization, demonstrating that the complex formed by (R)-SAL and β-cyclodextrin is stronger than the complex of (S)-SAL and β-cyclodextrin.…”
Section: Methodssupporting
confidence: 89%
“…packed with silica gel modified with β-cyclodextrin (MachereyNagel, Düren, Germany) kept at 30°C; (2) an isocratic pump adjusted to 0.80 ml/minute (Shimadzu LC-10AD, Kyoto, Japan); and (3) an LC-4C BAS amperometric detector (ED) set at a potential of 0.7 V. The mobile phase was 100 mM ammonium acetate containing 10 mM triethylamine (pH 4.0). Under these conditions and using a similar chiral HPLC system, it was reported that (S)-SAL was the first to elute (Baum & Rommelspacher 1994;Deng et al 1995;Naoi et al 1996;Liu et al 2000;Tóth et al 2001;Quan et al 2005;Cai & Liu 2008;Rojkovicova et al 2008;Huang et al 2009;Lee et al 2010).…”
Section: Experiments 1 Preparation Of Purified (R)-sal and (S)-sal Frmentioning
confidence: 99%
See 1 more Smart Citation
“…Three endogenous alkaloids were proposed as potential candidates of dopaminergic neurotoxins named salsolinol 2,3,Sal), tetrahydropapaveroline (THP) derivative (1BnTIQ) and β-carbolines. Sal, in particular, is toxic to dopaminergic neurons and has recently gained much attention due to its structural similarity with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, a potent neurotoxin that specifically degenerates the nigrostriatal dopaminergic neurons, resulting in dopamine deficiency in the striatum, and hence the symptoms of Parkinsonism (Quan et al 2005). Therefore, Sal may have an influential role directly or indirectly in causing PD.…”
Section: Introductionmentioning
confidence: 99%
“…Enantiomeric separation of dopamine-derived neurotoxins was performed with b-CD as chiral selector [163]. This group showed that the addition of a surfactant improved the recovery rates of these compounds from the deproteinization procedure.…”
Section: Biomedical Applicationsmentioning
confidence: 99%